Nevus Lipomatosus Cutaneous Superficialis - Paola M. Castro Zayas; Aihab Aboukheir Aboukheir; Atenas Martínez Bernal; Victor Ortíz Justiniano (Elsevier, 2021)
Nevus Lipomatosus Cutaneous Superficialis, also called a dermolipoma, is an uncommon benign hamartomatous skin tumor characterized by deposition of mature adipose tissue within the collagen of the dermis. Two types have been described: 1) solitary and 2) multiple, which is more common at the lower back. We report a case of an uncommon benign condition of a 11-year-old male with non-congenital Nevus Lipomatosus Cutaneous Superficialis in the lumbar region. Patient has a 7-year history of growth that started as a single nodule developing into multiple skin-colored pedunculated lesions associated with back pain. MRI of the lumbosacral spine with and without contrast showed evidence of a 10.7 × 7.7 × 2.6 cm low back nevus lipomatosus cutaneous superficialis with well-preserved underlying soft tissue and bony structures. Histopathological findings confirmed the diagnosis after an effective surgical excision without complications. Nevus Lipomatosus Cutaneous Superficialis is an uncommon benign condition that can be misdiagnosed during childhood. It is important to be able to recognize it in early stages because it can grow to very large sizes causing not only medical concerns but also aesthetic and self-esteem issues to patients.